Diversidad de hormigas en sistemas agroforestales de café contrastantes, en Turrialba, Costa Rica - Hilje, Luko; Hanson, Paul; Longino, John T.; Barbera, Nadiejda; Carballo, Manuel; Melo, Elias de (CATIE, Turrialba (Costa Rica), 2015)
3 ilus. 6 tab. 11 ref.